Smartphone Psychological Therapy During COVID-19: A Study on the Effectiveness of Five Popular Mental Health Apps for Anxiety and Depression - Marshall, Jamie M.; Dunstan, Debra A.; Bartik, Warren (Frontiers in Psychology, 2021)
The aims of this study were to examine the effectiveness of a range of smartphone apps for managing symptoms of anxiety and depression; and, to assess the utility of a single-case research design for enhancing the evidence base for this mode of treatment delivery. The study was serendipitously impacted by the COVID-19 pandemic, which allowed for effectiveness to be additionally observed in the context of significant community distress. A pilot study was initially conducted using the SuperBetter app to evaluate the proposed methodology, which proved successful with the four finishing participants. In the main study, 39 participants commenced (27 females and 12 males, MAge = 34.04 years, SD = 12.20); with 29 finishing the intervention phase and completing post-intervention measures. At six-month follow-up, a further three participants could not be contacted. This study used a digitally enhanced, multiple baseline across-individuals single-case research design. Participants were randomly assigned to the following apps: SuperBetter (n = 8), Smiling Mind (n = 7), MoodMission (n = 8), MindShift (n = 8), and Destressify (n = 8). Symptomatology and life functioning were measured at five different time points: pre-baseline/screening, baseline, intervention, three-week post-intervention, and six-month follow-up. Detailed individual perceptions and subjective ratings of the apps were also obtained from participants following the study’s completion. Data were analysed using visual inspection, time-series analysis, and methods of statistical and clinical significance pioneered by Jacobson and Truax (1991). Positive results were observed for all apps. Overall, more favourable outcomes were achieved by younger participants, those concurrently undertaking psychotherapy and/or psychotropic medication, those with anxiety and mixed anxiety and depression rather than standalone depression, and those with a shorter history of mental illness. Outcomes were generally maintained at six-month follow-up. It was concluded that a diverse range of evidence-based therapies offered via apps can be effective in managing mental health and improving life functioning even during times of significant global unrest and, like all psychotherapies, are influenced by client features. Additionally, this single-case research design is a low cost / high value means of assessing the effectiveness of mental health apps.